ANALYSIS OF TAX POLICY EFFECTIVENESS IN THE DIGITAL AGE IN DEVELOPING COUNTRIES - Fittry Megasari Sijabat (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
In the digital age, developing countries are faced with unique challenges in implementing effective tax policies. Technological developments have facilitated international transactions, but also made tracking and measuring economic activity more complex. Many developing countries still rely on traditional tax systems that are less capable of handling the dynamics of the digital economy. This study examines the effectiveness of various digital tax policies that have been implemented in several developing countries, while evaluating the most successful strategies. The analysis shows that strengthening tax administration capacity and international collaboration are key to reducing tax avoidance and increasing revenue from the digital sector. In addition, the adoption of new technologies, such as big data and artificial intelligence, as well as improving digital literacy among tax officials, are crucial for the successful implementation of tax policies in the digital era. With the right approach, developing countries have great potential to improve the effectiveness of their tax policies and optimally utilise the development of the digital economy.